Assessment of flamelet versus multi-zone combustion modeling approaches for stratified-charge compression ignition engines. (March 2016) - Pal, Pinaki; Keum, SeungHwan; Im, Hong G
The spray-interactive flamelet and extended multi-zone combustion models coupled with multi-dimensional computational fluid dynamics are applied to investigate the effects of charge stratification in a direct-injection compression ignition engine under low load conditions. A parametric study was carried out in order to compare the two approaches for early and late fuel injection timings. Comparison of numerical results with available experimental data shows that for early fuel injection, both models predict the auto-ignition and combustion characteristics with comparable fidelity. As the fuel injection timing is delayed, however, the spray-interactive flamelet model is found to capture the onset of combustion and subsequent heat release with greater accuracy. Further investigation reveals that the better performance of the spray-interactive flamelet model over a wider range of mixture-stratified conditions is mainly attributed to its ability to capture the diffusive transport resulting from small-scale mixing and turbulence–chemistry interaction, which becomes more important when significant mixture inhomogeneities exist in the engine cylinder.